Humoral and cellular immune response and safety of two‐dose SARS‐CoV‐2 mRNA‐1273 vaccine in solid organ transplant recipients. Issue 12 (4th August 2021) - Hall, Victoria G.; Ferreira, Victor H.; Ierullo, Matthew; Ku, Terrance; Marinelli, Tina; Majchrzak‐Kita, Beata; Yousuf, Anila; Kulasingam, Vathany; Humar, Atul; Kumar, Deepali
Abstract : Solid organ transplant recipients are at high risk of severe disease from COVID‐19. We assessed the immunogenicity of mRNA‐1273 vaccine using a combination of antibody testing, surrogate neutralization assays, and T cell assays. Patients were immunized with two doses of vaccine and immunogenicity assessed after each dose using the above tests. CD4+ and CD8+ T cell responses were assessed in a subset using flow‐cytometry. A total of 127 patients were enrolled of which 110 provided serum at all time points. A positive anti‐RBD antibody was seen in 5.0% after one dose and 34.5% after two doses. Neutralizing antibody was present in 26.9%. Of note, 28.5% of patients with anti‐RBD did not have neutralizing antibody. T cell responses in a sub‐cohort of 48 patients showed a positive CD4+ T cell response in 47.9%. Of note, in this sub‐cohort, 46.2% of patients with a negative anti‐RBD, still had a positive CD4+ T cell response. The vaccine was safe and well‐tolerated. In summary, immunogenicity of mRNA‐1273 COVID‐19 vaccine was modest, but a subset of patients still develop neutralizing antibody and CD4+T‐ cell responses. Importantly polyfunctional CD4+T cell responses were observed in a significant portion who were antibody negative, further highlighting the importance of vaccination in this patient population. IRB Statement: This study was approved by the University Health Network Research Ethics Board (CAPCR ID 20–6069). Abstract : This study shows that although transplant recipients' antibody and neutralization response to the mRNA‐1273 COVID‐19 vaccine are suboptimal, a cohort of antibody‐negative patients still generate SARS‐CoV‐2 specific T cell responses that may protect from severe disease.